2003
DOI: 10.1104/pp.102.016881
|View full text |Cite
|
Sign up to set email alerts
|

Nylon Filter Arrays Reveal Differential Gene Expression in Proteoid Roots of White Lupin in Response to Phosphorus Deficiency

Abstract: White lupin (Lupinus albus) adapts to phosphorus deficiency (ϪP) by the development of short, densely clustered lateral roots called proteoid (or cluster) roots. In an effort to better understand the molecular events mediating these adaptive responses, we have isolated and sequenced 2,102 expressed sequence tags (ESTs) from cDNA libraries prepared with RNA isolated at different stages of proteoid root development. Determination of overlapping regions revealed 322 contigs (redundant copy transcripts) and 1,126 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 82 publications
8
142
1
2
Order By: Relevance
“…2). These results are in agreement with results from the smaller microarrays with Arabidopsis, rice, and white lupin showing similar patterns of gene expression (7)(8)(9)(10). The differential expression of Pi-responsive genes is considered an adaptive response by plants to Pi deficiency, which facilitate acquisition of sparingly available Pi and concurrent attenuation of some of the energy-requiring metabolic pathways (21).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…2). These results are in agreement with results from the smaller microarrays with Arabidopsis, rice, and white lupin showing similar patterns of gene expression (7)(8)(9)(10). The differential expression of Pi-responsive genes is considered an adaptive response by plants to Pi deficiency, which facilitate acquisition of sparingly available Pi and concurrent attenuation of some of the energy-requiring metabolic pathways (21).…”
Section: Resultssupporting
confidence: 80%
“…This technical limitation has now been circumvented by recently developed microarray technology, which has been used successfully to study the effects of different abiotic stresses to large number of plant genes in parallel (6). To date, relatively small microarrays containing probes for less than one-third of all genes have been used in Arabidopsis, rice, and white lupin to monitor molecular responses to Pi deprivation (7)(8)(9)(10). In Arabidopsis, the expression of Ϸ29% of 6,172 genes examined changed in response to Pi starvation for up to 3 days (10).…”
mentioning
confidence: 99%
“…Moreover, white lupin roots impaired for endogenous auxin transport by being grown in the presence of the auxin transport inhibitor N-1-naphthylphthalamic acid failed to form induced cluster roots under P deficiency (Gilbert et al, 2000). Many genes involved in auxin synthesis and signaling are abundantly expressed in developing cluster roots of white lupin (Uhde-Stone et al, 2003b;Vance et al, 2003;Yamagishi et al, 2011). These data clearly show that a significant component of P-induced cluster root formation is due to auxin synthesis and transport.…”
Section: Hormones Are Involved In Lupin Cluster Root Developmentmentioning
confidence: 51%
“…They postulated that auxin stimulates the emergence of cluster rootlets in P-deficient plants, which results in increased production of cytokinin due to the numerous emerged root tips. In mature segments of P-induced cluster roots, we have found ESTs that annotate to cytokinin oxidase (CKX; Uhde-Stone et al, 2003b), suggesting that cytokinins are involved in cluster root development and maturation. We have recently transformed white lupin roots with a white lupin CKX:GUS reporter and a Medicago cytokinin receptor (CRE):GUS reporter.…”
Section: Hormones Are Involved In Lupin Cluster Root Developmentmentioning
confidence: 99%
“…Recent advances in post-genomic studies have indicated that transcriptomic analysis is a useful tool for understanding gene expression networks. Some transcriptomic studies of www.intechopen.com low-P adaptation strategies have also been carried out using cDNA arrays (Hammond et al, 2003;Misson et al, 2005;Ramaekers et al, 2010;Uhde-Stone et al, 2003;Wang et al, 2002;Wasaki et al, 2003bWasaki et al, , 2006Wu et al, 2003). Although some aspects of plant strategies for coping with P-deficient conditions are understood, the majority are not; a broad view of gene expression is necessary to fully elucidate all of the mechanisms involved (Ramaekers et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%